Avaliação do estado nutricional e fatores associados em idosos do sul do Brasil - Stoffel, Luciana Marcon Barbosa (2017)
The human aging process causes physiological, physical, and mental changes that may cause nutritional deficiencies. Several factors lead to reduced food intake by the elderly such as reduction of taste and smell, pathologies, oral health impact, early satiety, and psychosocial and medication-related factors. The selection of adequate food aids the reduction of nutritional risk and/or malnutrition. To assess malnutrition in the elderly, one of the instruments for nutritional screening that may be used is the Mini Nutritional Assessment (MNA™). This study assessed the nutritional status and its associated factors in the elderly of a city in southern Brazil. It is a homebased cross-sectional observational study performed with people aged from 65 to 74 years, living in residential homes in the city of Cruz Alta, RS, Brazil. The MNA™ was used for nu tritional analysis, as well as a structured questionnaire for socioeconomic conditions, an oral health clinical examination, and an anthropometric examination. Associations between the dependent variable and independent variables were assessed by either chi-square or Mann-Whitney tests, and presented by frequency distribution. The significance level was 5%. Poisson regression models were used to assess the association between nutritional risk and explanatory variables. Two hundred and eighty-seven (287) elderly people were interviewed and examined. The mean age was 69.30 years, from which 102 (35.5%) were men and 185 (64.5%) were women. One hundred and thirty-nine (139) elderly people (48.4%) were diagnosed with nutritional risk, and nine of these were diagnosed with malnutrition. With this, the results will be presented in production I. The access to the dentist over the last 12 months (p=0.002) and edentulous people with no complete denture or only one complete denture (p=0.006) were associated with nutritional risk.The findings of the present study showed a high prevalence of nutritional risk. The lack of complete or partial rehabilitation of edentulous people and the lack of access to the dentist over the last 12 months were associated with higher nutritional risk. The results suggest the need for an improvement in nutritional conditions of the elderly, including better oral health conditions.